Sum Of Fourth Powers?

Calculus Level 2

lim n n 5 1 4 + 2 4 + + n 4 = ? \lim_{n\to\infty} \dfrac{n^5}{1^4+2^4+\cdots+ n^4} = \, ?

Bonus : Generalize this.


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Rishabh Jain
Jul 21, 2016

Relevant wiki: Riemann Sums

See Reimann Sums U = lim n n p + 1 1 p + 2 p + 3 p + n p r = 1 n r p \mathcal U=\displaystyle\lim_{n\to\infty}\dfrac{n^{p+1}}{\underbrace{1^p+2^p+3^p\cdot +n^p}_{\displaystyle\sum_{r=1}^{n}r^{p}}}

= 1 lim n 1 n r = 1 n ( r n ) p = 1 0 1 x p d x = p + 1 ~~~=\dfrac{1}{\displaystyle\lim_{n\to\infty}\dfrac 1n\displaystyle\sum_{r=1}^{n}\left(\dfrac rn\right)^{p}}=\dfrac{1}{\displaystyle\int_0^1 x^p\mathrm{d}x}=\boxed{p+1}


For this question ,put p = 4 p=4 , so that:-

lim n n 5 1 4 + 2 4 + + n 4 = 5 \lim_{n\to\infty} \dfrac{n^5}{1^4+2^4+\cdots+ n^4} =\boxed{\color{#D61F06}{5}}

Greattttt

Challenge Master Note : Now solve this question without using Riemann Sums.

Pi Han Goh - 4 years, 10 months ago

Log in to reply

Then we can use : r = 1 n r 4 = n ( n + 1 ) ( 2 n + 1 ) ( 3 n 2 + 3 n 1 ) 30 \sum_{r=1}^n r^4=\dfrac{n(n+1)(2n+1)(3n^2+3n-1)}{30}

Rishabh Jain - 4 years, 10 months ago

Log in to reply

Second Challenge Master Note : This time, solve this question without using Riemann Sums nor the closed form for r = 1 n r 4 \displaystyle \sum_{r=1}^n r^4 .

Pi Han Goh - 4 years, 10 months ago

We note that lim n n m + 1 1 m + 2 m + 3 m + . . . + n m = a n b n \begin{aligned} \lim_{n \to \infty} \dfrac {n^{m+1}}{1^m + 2^m + 3^m + ... + n^m} = \frac {a_n}{b_n} \end{aligned} is such that 0 < b 1 < b 2 < . . . < b n < . . . 0 < b_1 < b_2 < ... < b_n < ... and lim n b n = \lim_{n \to \infty} b_n = \infty is a / \infty/\infty case and we can apply Stolz–Cesàro theorem as follows:

L = lim n n m + 1 1 m + 2 m + 3 m + . . . + n m = lim n a n + 1 a n b n + 1 b n = lim n ( n + 1 ) m + 1 n m + 1 k = 1 n + 1 k m k = 1 n k m By binomial expansion = lim n ( n m + 1 + ( m + 1 ) n m + ( m + 1 ) m 2 n m 1 + . . . + 1 ) n m + 1 ( n + 1 ) m = lim n ( m + 1 ) n m + ( m + 1 ) m 2 n m 1 + ( m + 1 ) m ( m 1 ) 2 n m 2 + . . . + 1 n m + m n m 1 + m ( m 1 ) 2 n m 2 + . . . + 1 Divide up and down by n m = lim n ( m + 1 ) + ( m + 1 ) m 2 n 1 + ( m + 1 ) m ( m 1 ) 2 n 2 + . . . + n m 1 + m n 1 + m ( m 1 ) 2 n 2 + . . . + n m = m + 1 \begin{aligned} L & = \lim_{n \to \infty} \dfrac {n^{m+1}}{1^m + 2^m + 3^m + ... + n^m} \\ & = \lim_{n \to \infty} \frac {a_{n+1}-a_n}{b_{n+1}-b_n} \\ & = \lim_{n \to \infty} \frac {\color{#3D99F6}{(n+1)^{m+1}}-n^{m+1}}{\sum_{k=1}^{n+1} k^m - \sum_{k=1}^{n} k^m} & \small \color{#3D99F6}{\text{By binomial expansion}} \\ & = \lim_{n \to \infty} \frac {\color{#3D99F6}{\left(n^{m+1}+(m+1)n^m + \frac {(m+1)m}2n^{m-1}+...+1\right)}-n^{m+1}}{(n+1)^m} \\ & = \lim_{n \to \infty} \frac {(m+1)n^m + \frac {(m+1)m}2n^{m-1}+ \frac {(m+1)m(m-1)}2n^{m-2}+...+1}{n^{m}+mn^{m-1} + \frac {m(m-1)}2 n^{m-2}+...+1} & \small \color{#3D99F6}{\text{Divide up and down by }n^m} \\ & = \lim_{n \to \infty} \frac {(m+1) + \frac {(m+1)m}2n^{-1}+ \frac {(m+1)m(m-1)}2n^{-2}+...+n^{-m}}{1+mn^{-1} + \frac {m(m-1)}2 n^{-2}+...+n^{-m}} \\ & = m+1 \end{aligned}

For m = 4 m=4 , the answer is m + 1 = 5 m+1 = \boxed{5} .

Great. Another approach is to show that 1 m + 2 m + 3 m + + n m = 1 m + 1 n m + 1 + O ( n m ) 1^m + 2^m + 3^m + \cdots + n^m = \dfrac1{m+1} n^{m+1} + O(n^m) .

Pi Han Goh - 4 years, 8 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...